Why Can High Charge‐Carrier Mobilities be Achieved Along π‐Conjugated Polymer Chains with Alternating Donor–Acceptor Moieties?. Issue 7 (28th May 2018) - Brédas, Jean‐Luc; Li, Yuan; Sun, Haitao; Zhong, Cheng
Abstract: Impressive charge‐carrier mobilities have been measured over the past few years for a number of well‐oriented π‐conjugated polymer chains. Intriguingly, these polymers frequently have complex chemical structures consisting of repeat units with alternating electron‐rich and electron‐poor moieties. A priori, such structures do not lend themselves to the presence of strongly dispersive valence or conduction electronic bands, which are required to achieve small charge‐carrier effective masses. Here, the factors that can lead to high carrier mobilities in the tens or even hundreds of square centimeter per volt per second are described briefly. Abstract : A number of well‐oriented π‐conjugated polymers, often with structures consisting of alternating, chemically different donor and acceptor moieties, have been reported to display high charge‐carrier mobilities. At first sight, such complex structures are not expected to lead to strongly dispersive valence or conduction electronic bands. Here, the factors that can bring carrier mobilities in the tens or even hundreds of square centimeter per volt per second are briefly described.